2010
DOI: 10.1016/j.acalib.2010.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Not on the Same Page: Undergraduates' Information Retrieval in Electronic and Print Books

Abstract: Academic libraries are increasingly collecting e-books, but little research has investigated how students use e-books compared to print texts. This study used a prompted think-aloud method to gain an understanding of the information retrieval behavior of students in both formats. Qualitative analysis identified themes that will inform instruction and collection practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
78
1
6

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(88 citation statements)
references
References 20 publications
(22 reference statements)
3
78
1
6
Order By: Relevance
“…In this study researchers observed and students reported using the Table of Contents (ToC) and the organization of books to make decisions. The importance of ToC, especially in ebooks, is reinforced by other studies [2,10]. This finding is also reflected in our companion work on book selection practices in physical libraries [8].…”
Section: Book Selectionsupporting
confidence: 66%
See 3 more Smart Citations
“…In this study researchers observed and students reported using the Table of Contents (ToC) and the organization of books to make decisions. The importance of ToC, especially in ebooks, is reinforced by other studies [2,10]. This finding is also reflected in our companion work on book selection practices in physical libraries [8].…”
Section: Book Selectionsupporting
confidence: 66%
“…Earlier studies show the frequent use of index for information seeking and decision-making within books in both physical [8] and digital formats [2]: a sharp contrast to the data seen here where only a few readers accessed the index. The reason for this discrepancy remains to be discovered.…”
Section: Document Selectioncontrasting
confidence: 54%
See 2 more Smart Citations
“…21 The study by Berg, Hoffman, and Dawson describes readers' treatment of e-books as "searching for discrete pieces of information." 22 Walton concludes, disapprovingly as the context of his discussion makes clear, "e-books are not being read FEAtURE but are used to find relevant information that will support an argument in a research paper." 23 Among faculty members, too, the same pattern remains: Jackson summarizes, "Faculty members.…”
Section: How E-books Are Used and By Whommentioning
confidence: 99%